Well-being and performance at work : the role of context - Peccei, Riccardo; Veldhoven, Marc Van (Psychology Press, Taylor & Francis Group, 2015)
"Organizational psychology has been interested in the well-being and performance of people at work for over a century, but our knowledge about both issues, and how they relate to each other, is still evolving. This important new collection provides new